A phase I trial evaluating the effects of plerixafor, G-CSF, and azacitidine for the treatment of myelodysplastic syndromes. Issue 6 (12th May 2021) - Huselton, Eric; Rettig, Michael P.; Fletcher, Theresa; Ritchey, Julie; Gehrs, Leah; McFarland, Kyle; Christ, Stephanie; Eades, William C.; Trinkaus, Kathryn; Romee, Rizwan; Kulkarni, Shashikant; Ghobadi, Armin; et al.
Abstract: Interactions between the bone marrow microenvironment and MDS tumor clones play a role in pathogenesis and response to treatment. We hypothesized G-CSF and plerixafor may enhance sensitivity to azacitidine in MDS. Twenty-eight patients with MDS were treated with plerixafor, G-CSF and azacitidine with a standard 3 + 3 design. Subjects received G-CSF 10 mcg/kg D1–D8, plerixafor D4–D8, and azacitidine 75 mg/m 2 D4–D8, but the trial was amended to reduce G-CSF dose to 5 mcg/kg for 5 days after 2 patients had significant leukocytosis. Plerixafor was dose escalated to 560 mcg/kg/day without dose limiting toxicity. Two complete responses and 6 marrow responses were seen for an overall response rate (ORR) of 36% in evaluable patients, and ORR of 53% in patients receiving the triplet. Evidence of mobilization correlated with a higher ORR, 60% vs. 17%. Plerixafor, G-CSF and azacitidine appears tolerable when given over 5 days and has encouraging response rates. KEY POINTS: Plerixafor and G-CSF can be safely combined with azacitidine for 5 days in patients with MDS. The overall response rate of 53% for evaluable patients with this regimen is higher than expected and more responses were seen in patients with blast mobilization.